2017
DOI: 10.23925/2176-2724.2017v29i1p2-9
|View full text |Cite
|
Sign up to set email alerts
|

Impactos da voz do professor na sala de aula: revisão da literatura

Abstract: Resumo Objetivo: Realizar uma revisão da literatura referente aos impactos da voz do professor no contexto da sala de aulaContribuição dos autores: ALVR concepção e planejamento do projeto; coleta de dados e análise dos dados; organização do texto. AMM concepção e planejamento do projeto; organização e revisão crítica do conteúdo. LCT concepção e planejamento do projeto; coleta e análise dos dados; organização e revisão crítica do conteúdo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Oral communication is a didactic work instrument in teaching. It offers information, increases students' interest, helps memorizing contents, strengthens the teaching -learning process and ensures the reliability of what is being said when it is well-applied and integrated (2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral communication is a didactic work instrument in teaching. It offers information, increases students' interest, helps memorizing contents, strengthens the teaching -learning process and ensures the reliability of what is being said when it is well-applied and integrated (2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…Most research about professors' voice focus voice health, but studies on professors' communicative skills are slowly starting to advance (1,4,5,12) . The interest in assessing professors' personal behavior comes from the fact that personality influences vocal production (13) ; moreover, this process is observed in the teaching process and in social interactions in classroom environment.…”
Section: Introductionmentioning
confidence: 99%
“…The naive people pointed out more the voices of slow speed, strong intensity and mild breathiness, which are supposed to meet the idea that the teacher's voice should convey clarity, authority and vitality, characteristics related to the psychodynamics of these voices (20) . Studies have pointed out that slow speed can favor the processing of the message in the classroom (4,23) and that strong intensity is one of the aspects of maintaining student's attention (4,8) . Regarding to the mild breathiness, it is believed that this acceptance is related to the mild degree of breathiness, which does not cause discomfort to the listener and is culturally associated with the aspect of female sensuality (20).…”
Section: Discussionmentioning
confidence: 99%
“…These voices are characterized by transmitting the sensation of fatigue, stress, weakness and exhaustion (20) . Studies have shown that the dysphonia has an unfavorable repercussion on the students (1,2,4,15,16) and that they present negative reactions to the dysphonic voice, characterizing it as rough, difficult to hear, repetitive, poor, sick and broken (2,15,16) . Table 3 shows that the voices of neutral vocal quality, bass pitch and slow speed were associated with a positive psychodynamic, desirable for a school context, because they were considered pleasant, motivating and able to arouse attention, which is in agreement with the literature found (8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation